1142 Safeguarding the Brains of Our Smallest Children: Safeboosc – the Pilot Study. (October 2012) - Hyttel-Sørensen, S; Austin, T; Benders, M; Claris, O; Dempsey, G; Fumagalli, M; Gluud, C; Hagmann, C; Hellström-Westas, L; Lemmers, P; Naulaers, G; Pellicer, A; et al.
Abstract : Background and Aims: The SafeBoosC project aims to test the benefits and harms of cerebral near-infrared spectroscopy (NIRS) oximetry in infants born before 28 weeks of gestation. A phase II trial will randomise infants to cerebral NIRS oximetry and a treatment guideline during the first 72 hours of life or standard care with blinded NIRS-monitoring. The primary outcome is the area (burden) outside the normal ranges of rStO2 of 55 to 85%. Methods: This pilot of the experimental group included 10 infants using the INVOS 5100C and NONIN EQUANOX 7600. Results: Median gestational age was 26 weeks + 3 days. Median start-up time was 133 minutes after delivery. Median recording time was 69.7 hours. Mean rStO2 was 64.2 +/- 4.5%. Median burden of hyper- and hypoxia was 30.3% hours (range 2.8–112.3). Clinical staff responded to out of range values 29 times – once was it to a value above 85%. In comparison, there was 83 periods of more than 10 minutes with rStO2 below 55% and four episodes with rStO2 above 85%. These periods accounted for 72% of the total burden of hypoxia. 18/29 of interventions were adjustments of FiO2 that 13 of 18 times resulted in an out of range SpO2 . Two infants suffered burns. Conclusions: Early cerebral NIRS monitoring proved feasible, but prolonged periods of hypoxia went untreated, while adjustment of FiO2 often would result in SpO2 out of local target range. This points to a less than perfect implementation of the treatment guideline.